LCMS and FTIR profiling of microalga Chlorella sp. for cosmetics and skin care applications - Ganeson, Yamuna; Paramasivam, Primilla; Palanisamy, Karthick Murugan; Govindan, Natanamurugaraj; Maniam, Gaanty Pragas (Elsevier, 2024)
People are exposed to extreme levels of UV radiation from the sun which gives a harmful effect on the skin. A prevention step should be taken such as applying a protective layer that able to protect the skin from UV rays. Hence, the protective layer should contain the antioxidant components that are able to prevent the formation of free radicals. Microalgae and the bioactive components that can be derived from them are thought to be viable raw material replacements in the cosmetics and pharmaceutical industries. In this study, carotenoid compounds with antioxidant characteristics such as neoxanthin and cryptoxanthin were successfully identified in Chlorella sp. by LC QTOF and the compounds have been reported to give a shield from skin aging. Meanwhile, the phenolic compounds were successfully identified through LC QTOF in Chlorella sp. that also been reported to be an active compound in sunscreen products. Besides, the identification of polysaccharide compounds was done by FTIR analysis, and the presence of the functional group was successfully identified. Polysaccharides have been reported to be an excellent anti-wrinkles characteristic. The alginate compound was analyses from the identification of a functional group based on the peaks formed. The alginate compound has been an excellent free radical scavenging. Therefore, Chlorella sp. can be applicable for cosmetics and skincare products as the antioxidant compounds such as phenolics compound, carotenoids, and polysaccharides have been identified.